PERANAN MAHASISWA EKONOMI DI UNIT KEGIATAN MAHASISWA BIDANG SENI (UKMBS) DALAM MENGEMBANGKAN KREATIVITAS DI KALANGAN MAHASISWA/I UNIVERSITAS BANDAR LAMPUNG - Mutiara Aura; Iskandar Ali Alam (Jurnal Widya, 2023)
This study aims to determine the role of art students in developing creativity among students at the University of Bandar Lampung. Art is all human actions that arise from feelings that are alive and beautiful in nature so that they can move the soul of human feelings. Art can be interpreted as the activity of creating forms that can be understood or perceived. Creativity is a mental process that involves the emergence of new ideas, is a person's ability to give birth to or create new things in the form of new or existing ideas or works. This study uses a qualitative method. Data collection techniques using interviews, observation, and documentation, data validity testing using triangulation techniques, data analysis techniques using inductive techniques. The role of art students in developing creativity among Bandar Lampung University students is urgently needed to encourage Bandar Lampung University students to develop the creativity and talents they have and fill their free time with useful things.